Adaptive learning concept selection: a bibliometric review of scholarly literature from 2011 to 2019 - Liliia O. Fadieieva (Academy of Cognitive and Natural Sciences, 2023)
The article describes the bibliometric analysis of scientific literature on adaptive learning in social sciences. With the selected documents, a cluster analysis was carried out according to the co-occurrence of keywords. As a result, the keywords were divided into five clusters, including ones associated with computer-aided instruction, engineering education, basic didactic principles, and individualized learning. The most interrelated keywords, primary keywords, and the chronological limits of the research were also determined from 2011 to 2019.